They know where you are [location detection]. - Warrior, J. (IEEE spectrum)
New technologies-including cellphone location systems, radio frequency identification tags, and ultrawideband receivers-can pinpoint your whereabouts. In this article, the authors argue that they may make you safer-but what about your privacy?.